The true nature of the portfolio balance channel of quantitative easing policy - Jakub Jakl (Review of Economic Perspectives, 2019)
This paper analyses the effects of the ECB's Public sector purchase programme (PSPP) on portfolios of the Eurozone investors. The ECB claims that the PSPP works mainly through the portfolio balance channel when the conditions on the asset markets are changed by the presence of a bidding central bank and investors are under those conditions forced to reallocate their portfolio to the state that better corresponds to ECB-changed market conditions and their preferences. This paper incorporates counterfactual analysis approach rather than analysis of direct change of prices and yields of given assets and uses sectoral data regression analysis of asset holdings of different investors in the Eurozone. This study addresses questions regarding size and direction of investors' reallocations - what types of investors were acting as the main counterparts to the ECB on the market for government bonds and what asset classes were preferred and chosen as an alternative by investors in the Eurozone to reallocate their funds. The series of obtained regression estimates and counterfactual analysis graphic representation answers to questions mentioned above and identifies a nonnegligible effect of the PSPP on the rebalancing of government bond portfolios towards riskier corporate bonds and equities across investor types in major Eurozone countries.
Keywords: E52; E61; G11; E65; 330; ECB; Portfolio Balance Channel; Public Sector Purchase Programme; Quantitative Easing